2020 European Thyroid Association Clinical Practice Guideline for the Use of Image-Guided Ablation in Benign Thyroid Nodules. Issue 4 (8th July 2020) - Papini, Enrico; Monpeyssen, Hervé; Frasoldati, Andrea; Hegedüs, Laszlo
Abstract : Standard therapeutic approaches for benign thyroid lesions that warrant intervention are surgery for cold and either surgery or radioiodine for autonomously functioning thyroid nodules (AFTN). Image-guided thermal ablation (TA) procedures are increasingly proposed as therapy options for selected clinical conditions. Due to mounting scientific evidence and widening availability, ETA considered it appropriate to develop guidelines for the use of TA in adult patients. TA procedures are well tolerated, but a dedicated training of the operators is required and information on possible complications needs to be shared with the patients. The following factors should be considered when weighing between observation, surgery, and TA for benign thyroid nodules. In solid non-hyperfunctioning nodules, TA induces a decrease in thyroid nodule volume, paralleled by improvement in symptoms. Nodule re-growth is possible over time and may necessitate repeat treatment, or surgery, in a dialogue with the patient. In AFTN, radioactive iodine is the first-line treatment, but TA may be considered in young patients with small AFTN due to higher probability of restoring normal thyroid function and avoidance of irradiation. In cystic nodules, ethanol ablation (EA) is the most effective and least expensive treatment. TA may be considered for cystic lesions that relapse after EA or have a significant residual solid component following drainage and EA. TA should be restricted to benign lesions that cause symptoms or cosmetic concern. Presently, laser and radiofrequency ablation are the most thoroughly assessed techniques, with similar satisfactory clinical results. Microwaves and high-intensity focused ultrasound therapy options remain to be fully evaluated.